The Synergistic Effect of Microwave Radiation and Hypergravity on Rats and the Intervention Effect of Rana Sylvatica Le Conte Oil - Wei Sun; Yudan Yang; Hongmei Yu; Luowei Wang; Su Pan (Dose-Response, 2017)
Aim: The phenomena of hypergravity and microwave radiation are widespread, which cause more and more concern for the hazards to human health. The aim of this study was to investigate the synergistic effect of microwave radiation and hypergravity on rats and observe the protective effect of Rana sylvatica Le conte oil. Methods: Rats were exposed to microwave radiation and hypergravity, and the rat weight, the climbing pole height, serum enzyme activities, blood urea nitrogen concentration, and total antioxidant capacity were detected. Results: The climbing pole height, the activities of choline acetyl transferase and cholinesterase, and the total antioxidant capacity decreased, whereas the activities of alanine aminotransferase, aspartate aminotransferase, areatine kinase, isocitric dehydrogenase, hydroxybutyrate dehydrogenase, and the blood urea nitrogen concentration increased in the hypergravity irradiation group as compared with the others. Conclusion: These results imply that the motion and nervous system of rats might be affected critically by the synergistic effect of microwave radiation and hypergravity, and it causes damage to most rat organs, such as the bone, skeletal muscle, liver, heart, and kidney, and the antioxidant effect is also damaged, while the injury resulted from it could be protected by Rana sylvatica Le conte oil.